ANTIMICROBIAL EFFECT OF VITAMIN C, VITAMIN E AND ESSENTIAL OIL OF ROMERO (Rosmarinus oficinalis) IN FRANKFURT CHICKEN SAUSAGES - Proaño Bastidas, Janeth (2017)
The antimicrobial effect of vitamin C, vitamin E and rosemary essential oil (Rosmaninus oficinalis) was determined. Twelve solutions at different concentrations, coupled with a control with butyl hydroxy toluene were prepared and applied to the chicken sausage frankfurters, which were subsequently vacuum packed and stored at 4 C for 30 days. The antimicrobial effect was determined by the use of specific agars for E coli, s. aureus, salmonella sp, mesophilic aerobes. The number of colony forming units (cfu) was quantified every five days for a period of 30 days. This method revealed that it was possible to completely inhibit the presence of Salmonella sp and E. coli. Moreover, aerobic mesophilic and S. aureus the amount of ufc aureus remained below accepted by the INEN Ecuador 1388 2010 standard limits. It is concluded that the applied treatments can replace chemical preservatives, maintaining the lifespan of the sausages for up to 30 days.